Determining the Factors Attracting the Tourists to Visit Kedah State, Malaysia - OMRAN, Abdelnaser; KAMRAN, Hafiz Waqas (Journal of Environmental Management and Tourism; Vol 9 No 2 (2018): JEMT Volume IX Issue 2(26) Spring 2018, 2018)
Among central approaches when studying the basic problems of the tourism geography, e.g. visitor’s relationship with a visited location is research on perception and image of visited locations, motivations, preferences, and experience of visitors. This study aimed to determine the impact of motivation to visit on the satisfaction with the respective visit to chosen types of locations attractions in the mountain and sub-mountain areas linked with the water component of the landscape. The study was carried out in the northern part of Malaysia specifically in Kedah State. A questionnaire survey was used to collect the required data. The targeted respondents were the visitors include both residents and non-residents who visited the attracted places in this mentioned state. This study could identify some useful motivational factors that cause an impact on the tourism industry in Kedah State, and it could also determine the level of satisfaction. The results revealed that beauty of scenery, cleanliness, hospitality and recommendation by friends are among the significant motivational factors in attracting tourists to visit the tourism destinations in Kedah State, whereas food, climate condition, personal safety, cleanliness and cultural diversity are of significant importance factors in attracting tourists to visit the State of Kedah.